2009
DOI: 10.1016/j.joen.2009.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Vertical Root Fractures in Endodontically Treated Teeth by a Cone Beam Computed Tomography Scan

Abstract: Our aim was to compare the accuracy of cone beam computed tomography (CBCT) scans and periapical radiographs (PRs) in detecting vertical root fractures (VRFs) and to assess the influence of root canal filling (RCF) on fracture visibility. Eighty teeth were endodontically prepared and divided into four groups. The teeth in groups A and B were artificially fractured, and teeth in groups C and D were not. Groups A and C were root filled. Four observers evaluated the CBCT scans and PR images. Sensitivity and speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
279
10
17

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(325 citation statements)
references
References 19 publications
16
279
10
17
Order By: Relevance
“…CBCT can assessing the vertical roots fractures under the influence of the root canal filling. Potentially, it demonstrated a highly accurate image compare to periapical radiographs [19]. In fact, CBCT also can be used to detect the horizontal root fractures as we can see in figure 3 (b).…”
Section: Traumatic Injuries and Sequelae Assessments:-assessments Of mentioning
confidence: 95%
“…CBCT can assessing the vertical roots fractures under the influence of the root canal filling. Potentially, it demonstrated a highly accurate image compare to periapical radiographs [19]. In fact, CBCT also can be used to detect the horizontal root fractures as we can see in figure 3 (b).…”
Section: Traumatic Injuries and Sequelae Assessments:-assessments Of mentioning
confidence: 95%
“…Yapılan ex-vivo çalışma-larda VKK'nın CBCT ile periapikal radyografilerden daha hassas tespit edildiği gösterilmiştir. 22 CBCT dento-alveolar travmaların teşhisinde faydalı olabilmektedir. 1,23,24 Alveolar lüksasyon yaralanmalarının yapısı ve şiddeti CBCT metodu ile herhangi bir geometrik distorsiyonuna ve anatomik görüntü bozukluğuna uğramadan tespit edilebilmektedir.…”
Section: Dental Travmaların Değerlendirilmesiunclassified
“…After flap elevation, the fracture line is visualized under light and magnification following staining with methylene blue (4). Superposition of the adjacent structures may complicate detection of fracture lines on periapical radiographs (5,6). A VRF may be visible on a periapical radiograph only when the fracture line and x-ray beam lie in the same plane or have a 4° difference at most (7).…”
Section: Introductionmentioning
confidence: 99%
“…Cone beam computed tomography (CBCT) is an advanced three-dimensional imaging technique studied for this purpose. However, presence of metal posts and some root canal filling materials may decrease its accuracy (5,10). Some previous studies compared the accuracy of conventional and digital intraoral radiography and CBCT for detection of VRFs and reported that CBCT and CT were significantly superior for this purpose (6), while some others reported similar accuracy of CBCT and digital radiography.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation